2008
DOI: 10.1111/j.1728-4457.2008.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Approaches to Measuring Women's Work in Developing Countries: A Comparison of Survey Data from Egypt

Abstract: Keyword and activities list approaches to measuring women's work are compared. The two approaches were applied to the same population of women in Egypt in two consecutive surveys. The widely used keyword approach underestimates women's work rates, disproportionately excluding poor and poorly educated women, particularly those working in nonformal jobs. The activities list approach captures these missed economic activities and also the multiple jobs women hold simultaneously. Survey measurement of women's work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 15 publications
1
32
0
3
Order By: Relevance
“…The trends in female labor force participation in rural areas must be interpreted with some caution, particularly in contrast with the explosive growth in the rural female market labor force in the 1998-2006 period. The difficulties in distinguishing between market and subsistence work, as well as participation and non-participation for rural women are well known (Anker 1990;Assaad 1997;Langsten and Salem 2008). Despite some caution in interpreting the trend in rural females' labor force participation, it is clear that overall the female labor force has contracted, despite growth in the working age population.…”
Section: Trends In Labor Force Participationmentioning
confidence: 99%
“…The trends in female labor force participation in rural areas must be interpreted with some caution, particularly in contrast with the explosive growth in the rural female market labor force in the 1998-2006 period. The difficulties in distinguishing between market and subsistence work, as well as participation and non-participation for rural women are well known (Anker 1990;Assaad 1997;Langsten and Salem 2008). Despite some caution in interpreting the trend in rural females' labor force participation, it is clear that overall the female labor force has contracted, despite growth in the working age population.…”
Section: Trends In Labor Force Participationmentioning
confidence: 99%
“…Some estimates have put this number higher, closer to 60%, when a broader definition of work is used (Langsten and Salem 2008). Recently in some countries in the Middle East and North Africa (MENA) region, such as Morocco and Tunisia, female labor force participation has begun to increase, yet Egypt lags behind its regional neighbors (Assaad 2004).…”
Section: Women's Labor and Leisurementioning
confidence: 99%
“…Research in Egypt has found that lists asking about participation in a set of possible activities are a good way to measure various types of women's work, as opposed to simply asking if someone works in the labor market (Langsten and Salem 2008). Activity lists allow women to identify various types of work that they do, thereby offering a fuller picture of the nature of the work.…”
Section: Figurementioning
confidence: 99%
“…O fficial labour force data are widely acknowledged to provide inadequate coverage of women's informal remunerative work. 1 This shortcoming stems from the definitions and conceptual categorizations of "work", and the way in which these are operationalized for data collection (Langsten and Salem, 2008;McDowell, 1999;Standing, 1999). Normative constructions around gender and work have important implications not only for how "work" is defined (Benería, 1999), but also for the way data are assembled, how survey questions are phrased and the answers interpreted (Anker, 1983;Mata Greenwood, 1999;Tomoda, 1985).…”
mentioning
confidence: 99%